Exurban Farmers' Perceptions of Land Use Policy Effectiveness: Implications for the Next Generation of Policy Development - Jill K. Clark; Shoshanah M. Inwood; Douglas Jackson-Smith (Journal of Agriculture, Food Systems, and Community Development, 2016)
Many local governments have enacted land use policies to address farmland loss and farm viability by protecting large blocks of farmland from residential growth. While the rate of suburban "sprawl" has slowed since the burst of the housing bubble in 2008, these policies remain the dominant approach to agricultural land use policy. Given the importance of exurban agricultural production, the growing diversity of exurban farms, and the increasing interest in local food systems by the public, it is time to revisit land use policy. Little is known about how farmers perceive land use policy environments, and whether diverse types of farmers have distinctive views on policy effectiveness. Therefore in this study we document land use policy environments of eight U.S. exurban counties. With farmer survey results we examine factors associated with farmers' perceptions of policy effectiveness. We find that the overall policy environment and differences in farmer and farm characteristics explain less variation in views of effectiveness than do farmers' perceptions of local community support, pressure from global markets, intensity of nonfarm development, and overall optimism about the future of agriculture. Farmers who market directly to consumers are particularly pessimistic about land use policies, as these policies were likely not designed with small farms in mind. Results suggest that next-generation policy efforts to encourage the sustainability of exurban farming could be more effective by creating stronger ties between farm and nonfarm populations, adopting flexible policies that recognize the different ways in which farmers adapt to urbanization, and ensuring that the voices of diverse exurban farmers are included in a participatory policy-making process.